2023
DOI: 10.3390/microbiolres14020052
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Antimicrobial Stewardship: Before, during and after the COVID-19 Pandemic

Omar Khaznadar,
Farah Khaznadar,
Ana Petrovic
et al.

Abstract: Antimicrobial resistance (AMR) is an ongoing phenomenon. It is a significant public health issue that has existed long before the coronavirus disease of 2019 (COVID-19) pandemic. It develops as microorganisms undergo genetic mutations that allow them to survive despite antimicrobial treatment. This process is highly associated with excessive and often unnecessary antimicrobial pharmacotherapy, which was often discussed during the COVID-19 pandemic. This article explores how the pandemic has affected antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Another study, conducted in a COVID-19 referral hospital in Iran, showed a significant overall resistance increase among Gram-negative bacteria, particularly P. aeruginosa and K. pneumoniae [ 25 ]. A review conducted by Khaznadar et al also revealed that Gram-negative pathogens were those with levels of antimicrobial resistance most affected by the overuse of antibiotics during the pandemic [ 26 ], while a retrospective study conducted in Greece showed an increasing trend in the incidence of resistant Gram-negative bacteria, particularly in ICUs, compared to the pre-pandemic period [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study, conducted in a COVID-19 referral hospital in Iran, showed a significant overall resistance increase among Gram-negative bacteria, particularly P. aeruginosa and K. pneumoniae [ 25 ]. A review conducted by Khaznadar et al also revealed that Gram-negative pathogens were those with levels of antimicrobial resistance most affected by the overuse of antibiotics during the pandemic [ 26 ], while a retrospective study conducted in Greece showed an increasing trend in the incidence of resistant Gram-negative bacteria, particularly in ICUs, compared to the pre-pandemic period [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous reports, which showed an increased AMR rate during the COVID-19 pandemic, particularly for Gram-negative bacteria, we hypothesize that the concomitant spread of SARS-CoV-2 may have partially facilitated the rapid dissemination of these MDR strains. This highlights the crucial need for strengthened infection prevention and control measures and enhanced antimicrobial stewardship in the post-pandemic era [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlighted a gradual increase in the prevalence of HAIs caused by Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae strains, particularly in the last two years of the study period, 2020 and 2021. Numerous recent scientific articles have demonstrated a significant rise in HAIs associated with these strains since the onset of the COVID-19 pandemic [24,25]. A review study published in June 2023 showed an overall increase in drug-resistant bacterial infections involving Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, and other germs, correlating with the heightened use of antibiotics in COVID-19 admissions [26].…”
Section: Discussionmentioning
confidence: 99%